FOSTERING AGROPRENEURSHIP PRACTICE IN NIGERIA: A LOOK BENEATH THE SURFACE - Olamitunji DAKARE (Management & Marketing)
Agropreneurship is a powerful tool for shaping today’s economic development. This article focuses on how governments, academics, and policymakers on agropreneurship programs can prepare both existing and potential agropreneurs to continue contributing to the economic growth and development of the country. This paper draws out the key findings of existing literature relating to the growing field of agropreneurship by critically and constructively reviewing literature that examines issues and perspectives on agropreneurship and the agricultural sector within the Nigeria context, especially with careful analysis of historical data and current data. The review is in line with the need to create sustainable development through agropreneurship initiatives: in an economy presently facing a high rate of unemployment, extreme poverty, poor earnings from foreign exchange, and insufficiency of food items, this article argues for the need to adopt an overarching agriculture value chain to ensure a rapid industrial and economic development across Nigeria. Therefore, an integrative framework for effective agropreneurship practice in Nigeria is proposed to build the capacity of the Nigerian agricultural system, which has a multiplier effect on both the socio-economic and industrial advancement of the country because of its multifunctional nature. Specific recommendations for the capacity of the Nigerian agricultural system through agropreneurship initiatives are offered.